2020
DOI: 10.1111/ene.14208
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on α‐synuclein in plasma neuronal exosomes as a biomarker for Parkinson’s disease development and progression

Abstract: Background and purpose: The identification of reliable diagnostic and prognostic biomarkers for Parkinson's disease (PD) is urgently needed. Here, we explored the potential use of a-synuclein (a-syn) in plasma neuronal exosomes as a biomarker for early PD diagnosis and disease progression. Methods: This study included both cross-sectional and longitudinal designs. The subjects included 36 patients with early-stage PD, 17 patients with advanced PD, 20 patients with idiopathic rapid eye movement sleep behavior d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 18 publications
6
127
2
1
Order By: Relevance
“…Similar phenomenon was observed that patients whose α-syn longitudinally increased underwent deterioration of motor symptom in the follow-up. 66 Some other studies confirmed the value of increased exosomal αsyn, oligomeric α-syn or the ratio of it to total α-syn in different biological fluids as biomarkers of PD. [67][68][69] Interestingly, Si et al reported α-syn level in CNSderived exosomes is lower in PD patients than essential tremor and healthy groups.…”
Section: Applications Of Evs In Cns Disease Neurodegenerative Diseasementioning
confidence: 92%
“…Similar phenomenon was observed that patients whose α-syn longitudinally increased underwent deterioration of motor symptom in the follow-up. 66 Some other studies confirmed the value of increased exosomal αsyn, oligomeric α-syn or the ratio of it to total α-syn in different biological fluids as biomarkers of PD. [67][68][69] Interestingly, Si et al reported α-syn level in CNSderived exosomes is lower in PD patients than essential tremor and healthy groups.…”
Section: Applications Of Evs In Cns Disease Neurodegenerative Diseasementioning
confidence: 92%
“…In addition, Spearman's correlation analysis revealed that neuronal exosomal α-synuclein concentrations were correlated with Movement Disorders Society UPDRS III/(I + II + III) scores, Non-Motor Symptom Questionnaire scores and Sniffin' Sticks 16-item test scores of patients with PD. After a mean follow-up of 22 months in patients with early-stage PD, a Cox regression analysis adjusted for age and gender showed that longitudinally increased α-synuclein rather than baseline α-synuclein levels were associated with higher risk for motor symptom progression in PD [37].…”
Section: Aimmentioning
confidence: 99%
“…Importantly, it has to be taken into account that the outcome depends from the source of the EVs carrying α-Syn, which can be plasma, serum or CSF. In fact, α-Syn detected in plasma deriving EVs may be also be produced by plasma cells [184,185].…”
Section: 'Flipping the Table': Evs As Potential Novel Pd Biomarkersmentioning
confidence: 99%